Development of Picture Storybook in Digital Form to Improve Language and Cognitive Ability Children of Group B in RA. Ash-Sholihah Medan Johor Academic Year 2021/2022 - Syaza Amirah; Aman Simare-mare; Daulat Saragi (Budapest International Research and Critics University, 2022)
The problem in this study is that the teacher has not used illustrated story books in digital form for storytelling activities, so that children are less interested in listening to the stories conveyed by the teacher. This study aims to develop illustrated story books in digital form to improve children's language and cognitive abilities. This type of research is research and development (Research & Development). The ADDIE development model consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The subjects in this study were group B students at R.A. Ash-Sholihah which amounted to 20 people, 10 men and 10 women. Then this research was validated by 3 validators, namely material experts, media experts and early childhood education practitioners. Determination of the feasibility of picture story books in digital form is based on expert validation tests, while effectiveness is based on improving children's language and cognitive abilities before (pretest) and after (posttest) using the media. From the results of the assessment that has been carried out by validator experts, material experts obtained an average score of 82% in the very feasible category, media experts obtained an average score of 84% in the very appropriate category, early childhood experts on average obtained a score of 84% in the category very feasible, educational practitioners obtained by 98.18% very decent category. Then the results of the children's worksheets get a pretest average value of 11.2 while the posttest average value of 17.4 in improving children's language skills using picture story books in digital form. The results of the pretest with an average of 11.0 and posttest with an average of 17.1 experienced an increase in children's cognitive using picture story books in digital form, it can be said that the use of digital media is very effective to use. It is hoped that teachers will be more creative and innovative in making picture story books in digital form, therefore schools must prepare facilities and infrastructure that can support learning.